Analysis of the Gastronomic Tourism Potential in the La Candelaria locality, Bogotá - Cote Daza, Sandra Patricia; Guzmán Jiménez, María Jimena; Quintero Hernández, Luisa Fernanda; Beltrán Virgüez, Jesús Enrique; Barón-Chivara, Jesús Alexis (Cuadernos de Administración, 2024)
Gastronomic tourism has established itself as a fundamental pillar for positioning tourist destinations by integrating ancestral knowledge, traditions, and the potential of products passed down through generations. According to the World Tourism Organization (WTO), gastronomic experiences are the primary travel motive for 30% of tourists. In Bogotá, various organizations are working to develop this type of tourism, although it is necessary to integrate existing studies to formulate a competitive proposal. This research aimed to diagnose the gastronomic situation in the La Candelaria locality. A qualitative methodology was used, beginning with an analysis of the territorial and touristic context, the supply, demand, potential, and trends of gastronomic tourism, following the proposal of the WTO and the Basque Culinary Center. Five in-depth interviews with experts were conducted to analyze and diagnose gastronomic tourism in La Candelaria. The results indicate that La Candelaria has a competitive advantage due to its accessibility to differentiated products. 101 establishments were identified on social networks, 40 preparations in the inventory of typical preparations, 6 gastronomic tours, 18 events/contests, and the La Concordia Market Square as elements that enhance gastronomic tourism. The study concludes that there is a value chain in gastronomic tourism in La Candelaria. However, it is necessary to update the sector’s figures and develop joint actions between the government and gastronomic establishments to maximize their potential.